2006
DOI: 10.1080/17461390601012637
|View full text |Cite
|
Sign up to set email alerts
|

Self‐determination, stage of readiness to change for exercise, and frequency of physical activity in young people

Abstract: Grounded in self-determination theory (Deci & Ryan, 1985) and the transtheoretical model (Prochaska & DiClemente, 1983), the aim of this study was to examine the relationship between exercise regulations varying in self-determination with stage of readiness to change for exercise and physical activity patterns in university students. A cross-sectional survey design was used. The sample consisted of 409 (158 men, 251 women) university undergraduates aged 18 Á30 years. Participants completed the Behavioural Regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 56 publications
10
63
2
6
Order By: Relevance
“…These results suggest people who engage in regular PA find PA more enjoyable, identify PA as a part of their self-concept, and value the benefits of PA. These findings have been supported in previous research (Dacey, Baltzell, & Zaichowksy, 2008;Daley & Duda, 2006). Similar effect sizes were found by Wininger and DeSena (2012) for intrinsic (ranged η 2 = .16 to η 2 = .29), integrated (η 2 = .32), and identified (η 2 = .22).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results suggest people who engage in regular PA find PA more enjoyable, identify PA as a part of their self-concept, and value the benefits of PA. These findings have been supported in previous research (Dacey, Baltzell, & Zaichowksy, 2008;Daley & Duda, 2006). Similar effect sizes were found by Wininger and DeSena (2012) for intrinsic (ranged η 2 = .16 to η 2 = .29), integrated (η 2 = .32), and identified (η 2 = .22).…”
Section: Discussionsupporting
confidence: 79%
“…After six months of regular PA, a person has achieved the target behavior, and is in the maintenance stage. Research has shown differences in constructs such as SDT (Daley & Duda, 2006), self-efficacy for exercise , and goal setting (Gladys et al, 2008) across stages of change. It is hypothesized that individuals within a higher stage of change will have more adaptive scores across all constructs within the ESRM.…”
Section: Transtheoretical Model: Stages Of Changementioning
confidence: 99%
“…The studies related to aspects of self-determinant theory and stages of exercise behavior change have shown that the participants in the high stages of exercise behavior change have more autonomy orientation and less control and impersonal orientations (Daley & Duda, 2006;Landry & Solmon, 2004;Rose et al, 2005). In general, they are self-determinant.…”
Section: Jpes ®mentioning
confidence: 99%
“…The longitudinal research of Fortier et al (2007)also showed that self-determination motive increases in the participants who exercise regularly for six months. Daley and Duda (2006)Also showed the men and women had lower self-determination in the first stages of behavior change than the participants in higher stages in the regulation of their behavior training. Moreover, the men and women who had more self-determination reported more physical activity during three last months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation